2017
DOI: 10.1007/s10865-017-9823-5
|View full text |Cite
|
Sign up to set email alerts
|

How people think about the chemicals in cigarette smoke: a systematic review

Abstract: Laws and treaties compel countries to inform the public about harmful chemicals (constituents) in cigarette smoke. To encourage relevant research by behavioral scientists, we provide a primer on cigarette smoke toxicology and summarize research on how the public thinks about cigarette smoke chemicals. We systematically searched PubMed in July 2016 and reviewed citations from included articles. Four central findings emerged across 46 articles that met inclusion criteria. First, people were familiar with very fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 62 publications
3
50
0
2
Order By: Relevance
“…These results suggest that many smokers in the clearly combustion segment retain a strong implicit belief that nicotine is very harmful and that thinking about nicotine evokes negative affective associations. These results are broadly consistent with both recent US findings and findings from our earlier qualitative research .…”
Section: Discussionsupporting
confidence: 92%
“…These results suggest that many smokers in the clearly combustion segment retain a strong implicit belief that nicotine is very harmful and that thinking about nicotine evokes negative affective associations. These results are broadly consistent with both recent US findings and findings from our earlier qualitative research .…”
Section: Discussionsupporting
confidence: 92%
“…This finding confirms and extends the previous findings of Hall et al and is consistent with other research on constituents 8 15. Health communication campaigns may still be able to productively focus on less familiar constituents; however, more research is needed on how to best address low understanding of these unfamiliar cigarette smoke constituents.…”
Section: Discussionsupporting
confidence: 90%
“…Our recent review of the literature found low awareness and knowledge about cigarette smoke constituents other than nicotine and tar 8–14. Additionally, our review also found that people are interested in learning more about these constituents 8 15 16. However, the literature has large gaps.…”
Section: Introductionmentioning
confidence: 76%
“…3 When asked what chemicals are in cigarettes, most people can name only nicotine, carbon monoxide, and “tar.” 49 The public has an interest in knowing more about the chemicals in cigarette smoke, 10–12 and some studies suggest that learning about the chemicals may increase quit intentions. 3 Some experts argue the public has a fundamental right to know what they are consuming when they smoke, just as they currently know what ingredients are in food. 13–15 …”
mentioning
confidence: 99%